Jojo's story - Moses, Antoinette (Cambridge English readers. Level 2, 2000)
There aren't any more days. There's just time. Time when it's dark and time when it's light. Everything is dead, so why not days too?" Everyone in Jojo's village is dead, and ten-year-old Jojo is alone